The Effect of a Video of the Story of Prophet Yusuf on Forgiveness in Children - Zun Azizul Hakim; Isnaini Amelia; Faradina Mutia; Riza Zahra; Zufri (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
Interpersonal forgiveness is a crucial component of psychological well-being and positive character development, particularly in children. Given the known efficacy of narrative-based learning and the profound moral depth of religious stories, this study aims to investigate the effectiveness of a video intervention based on the story of Prophet Yusuf (Joseph) in enhancing forgiveness among children.The study employed a quantitative experimental design using a Nonrandomized Pretest-Posttest Control Group Design. Participants were 20 children from the Rangkang Pustaka Community, divided equally into an experimental group (receiving the video intervention) and a control group (no intervention). Forgiveness was measured using an adapted Forgiveness Scale before and after the treatment.The results of the Independent Samples t-test showed a statistically significant difference between the posttest scores of the experimental group (Mean = 29.90) and the control group (Mean = 26.20), with t(18)=2.842 and p=0.011 (α=0.05). This finding confirms the rejection of the null hypothesis.In conclusion, the video intervention based on the story of Prophet Yusuf is an effective and highly practical tool for significantly increasing children's forgiveness levels. The study recommends integrating culturally and spiritually relevant narratives into character education programs to foster prosocial behavior.